Post-partum invasive group B streptococcus infection with fatal outcome: a case report - Zakariah, Siti Zulaikha; Zainun, Khairul Anuar; Md Najib, Asyraff; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Group B streptococcus (GBS) is generally known to cause severe disease in the neonate and immunocompromised adults. GBS in the pregnant mother is rare and can potentially be fatal. Clinical presentation can be as mild as an uncomplicated urinary tract infection or serious invasive disease in the form of bacteremia, chorioamnionitis, endometritis and septic abortion. We report a case of a 46-year-old Para 3 lady, post-partum day 12, whom was found dead at home. Prior to her death, she had intermittent fever and abnormal lochia. Autopsy findings indicate GBS endometritis and bacteraemia. She was never screened for GBS. The cost-effectiveness of universal GBS screening needs to be explored to reduce maternal and neonatal morbidity due to GBS.